Analisis Pengendalian Kualitas menggunakan Lean Six Sigma dan Kaizen (Studi Kasus pada Hilton Konveksi) - Indah Lestari, Dwi Ayu; Miharja, Rediawan (Fakultas Bisnis, 2025)
The garment manufacturing industry in Indonesia faces ongoing challenges in maintaining consistent product quality, as seen at Hilton Konveksi, where defect rates often exceed the acceptable 1% tolerance limit. This study aims to identify the root causes of product defects in the production of work trousers and propose structured improvements to enhance quality control. Using the Lean Six Sigma methodology integrated with the DMAIC (Define, Measure, Analyze, Improve, Control) framework and supported by the Kaizen philosophy, the research provides a systematic and data-driven approach to process optimization. Data were collected through observation, interviews, check sheets, and company documentation. The results show that the average defect rate reached 5.1%, with slanted stitching being the most frequent issue, accounting for 36% of total defects. Root cause analysis using the 5M (Man, Machine, Method, Material, Environment) framework revealed multiple contributing factors, including operator fatigue, lack of SOPs, and inadequate equipment maintenance. Kaizen-based improvement recommendations were implemented, focusing on preventive actions and employee involvement. The calculated sigma level of 3.61 indicates moderate process capability. Overall, the study demonstrates that the integration of Lean Six Sigma and Kaizen can effectively reduce defects, improve product quality, and enhance operational efficiency in garment manufacturing.